Differential gene expression in patients with anal fistula reveals high levels of prolactin receptor - Song, Yi-huan; Qiu, Jian-ming; Yang, Guan-gen; Wang, Dong; Lin, A-li; Xu, Kan (Vojnosanitetski pregled, 2017)
Background/Aim. There are limited data examining variations in the local expression of inflammatory mediators in anal fistulas where it is anticipated that an improved understanding of the inflammatory milieu might lead to the potential therapeutic option of instillation therapy in complicated cases. The aim of the present study was to examine prolactin receptors (PRLR) as inflammatory markers and to correlate their expression with both the complexity of anal fistulas and the likelihood of fistula recurrence. Methods. Microarray was used to screen the differentially expressed gene profile of anal fistula using anal mucosa samples with hemorrhoids with age- and sex-matched patients as controls and then a prospective analysis of 65 patients was conducted with anal fistulas. PRLR immunohistochemistry was performed to define expression in simple, complex and recurrent anal fistula cases. The quantitative image comparison was performed combining staining intensity with cellular distribution in order to create high and low score PRLR immunohistochemical groupings. Results. A differential expression profile of 190 genes was found. PRLR expression was 2.91 times lower in anal fistula compared with control. Sixty-five patients were assessed (35 simple, 30 complex cases). Simple fistulas showed significantly higher PRLR expression than complex cases with recurrent fistulae showing overall lower PRLR expression than de novo cases (p = 0.001). These findings were reflected in measurable integrated optical density for complex and recurrent cases (complex cases, 8.31 ± 4.91 ´ 104 vs simple cases, 12.30 ± 6.91 ´ 104; p < 0.01; recurrent cases, 7.21 ± 3.51 ´ 104 vs primarily healing cases, 8.31 ± 4.91 ´ 104; p < 0.05). In univariate regression analysis, low PRLR expression correlated with fistula complexity; a significant independent effect maintained in multivariate analysis odds ratio [(OR) low to high PRLR expression = 9.52; p = 0.001)]. Conclusion. PRLR expression inversely correlates with anal fistula complexity. Further work must define the specificity of this finding and its relationship to other conventional mediators of inflammation.
Keywords: rectal fistula; receptors; prolactin; gene expression; immunohistochemistry; biological markers